2019
DOI: 10.1007/s00590-019-02402-w
|View full text |Cite
|
Sign up to set email alerts
|

Adjacent Bi-level bilateral pedicle stress fractures after instrumented posterolateral lumbar fusion—a case report and review of the literature

Abstract: Isolated bilateral pedicle stress fractures of the lumbar spine are rare events, and few cases are reported in the literature. Their occurrence is commonly related to post-operative complications of spine instrumentation but can also be associated with stress-related activities, degenerative spine conditions, trauma and other miscellaneous causes. The authors report a case of adjacent bi-level bilateral pedicle fracture that developed 5 years after an instrumented posterolateral lumbar fusion. We believe that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 33 publications
0
5
0
Order By: Relevance
“…To the best of our knowledge, there have been seven case reports of pedicle fracture associated with posterior instrumentation surgery of the lumbar spine. [7][8][9][10][11][12][13] However, in three cases, the fracture occurred at the adjacent vertebrae, and another case was associated with implant removal. [7][8][9][10] The remaining three cases had pedicle fractures within the fusion range without implant removal, but all of them had experienced middle to long posterolateral fusion (PLF) using a hook-and-rod system with no use of pedicle screws.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…To the best of our knowledge, there have been seven case reports of pedicle fracture associated with posterior instrumentation surgery of the lumbar spine. [7][8][9][10][11][12][13] However, in three cases, the fracture occurred at the adjacent vertebrae, and another case was associated with implant removal. [7][8][9][10] The remaining three cases had pedicle fractures within the fusion range without implant removal, but all of them had experienced middle to long posterolateral fusion (PLF) using a hook-and-rod system with no use of pedicle screws.…”
Section: Discussionmentioning
confidence: 99%
“…[7][8][9][10][11][12][13] However, in three cases, the fracture occurred at the adjacent vertebrae, and another case was associated with implant removal. [7][8][9][10] The remaining three cases had pedicle fractures within the fusion range without implant removal, but all of them had experienced middle to long posterolateral fusion (PLF) using a hook-and-rod system with no use of pedicle screws. [11][12][13] Chiang et al 14 reported a case of L5 vertebral fracture and L5-S1 spondylolisthesis at 3 months after L3-5 transforaminal lumbar interbody fusion (TLIF).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[4] Case report Unilateral L4 Contralateral spondylosis Guillodo et al [5] Case report Unilateral L5 Contralateral spondylosis Vialle et al [6] Case report Unilateral L5 Contralateral spondylosis Weatherley et al [7] Case report, review Unilateral L4 Contralateral spondylosis Carr et al [8] Case report, review Unilateral L2-3 Spondylolisthesis, scoliosis Kim et al [9] Case report Unilateral L5 Spondylolytic spondylolisthesis Guo et al [10] Case report Unilateral L5 Back massage, spondylolytic spondylolisthesis Ha and Kim [11] Case report Bilateral L4 Revision spinal surgery Knight and Chan [12] Case report Not mentioned L3 Scoliosis, posterior spinal fusion Macdessi et al [13] Case report Bilateral L4 Revision spinal surgery Robertson and Grobler [14] Case report Bilateral L3 Revision spinal surgery Sheehan et al [15] Case report Unilateral L4 Previous spinal surgery Stanley and Smith. [16] Case report Unilateral L4 Previous spinal surgery Tribus and Bradford [17] Case report Bilateral L4 Scoliosis, posterior spinal fusion Jorge and Carvalho [18] Case report Bilateral L2-3 Previous spinal surgery Kim et al [19] Case report Bilateral L4 Osteoporosis, previous spinal surgery Parvataneni et al [20] Case report Bilateral L5 Athlete Tahir and Islam [21] Case report Bilateral L4 Amateur weightlifting Mohapatra et al [23] Case report Bilateral L4 Osteopetrosis, spondylolysis Doita et al [24] Case report Bilateral L4 Osteoporotic compression fracture of L5 Kim et al [25] Case report Bilateral L4 Osteoporosis, L4-5 spinal stenosis Maruo et al [29] Case report Unilateral L5 Long-term hemodialysis, spondylolisthesis, degenerative scoliosis, destructive spondyloarthropathy neurogenic claudication and muscle weakness of the right lower limb, evidence of degenerative lumber scoliosis and Grade I isthmic spondylolisthesis at L5-S1, with later progression to destructive spondyloarthropathy and progression of the lumbar curve and slippage with resultant unilateral pedicle fracture at the concavity of L4-5. erefore, the patient underwent gill laminectomy of the L5 with pedicle screw fixation at L4-S1 and interbody fusion using the posterior lumbar interbody fusion technique.…”
Section: Study Type Laterality Level Risk Factorsmentioning
confidence: 99%
“…[1,2] It is rare to have an atraumatic lumbar pedicle fracture, but it is possible in predisposed patients, as mentioned in many reports. Some reported cases with pedicle fractures were predisposed by contralateral spondylolysis or degenerative spondylolisthesis [3][4][5][6][7][8][9][10] by the previous spine surgical intervention [11][12][13][14][15][16][17][18][19] by stressful physical activities [5,20,21] or predisposed by metabolic bone diseases. [19,[22][23][24][25] However, two reported cases of one-level pedicle fracture without significant trauma, previous surgical intervention, or a bony abnormality exist.…”
Section: Introductionmentioning
confidence: 99%